2019
DOI: 10.1002/macp.201900414
|View full text |Cite
|
Sign up to set email alerts
|

3D Network Binder via In Situ Cross‐Linking on Silicon Anodes with Improved Stability for Lithium‐Ion Batteries

Abstract: Silicon (Si) has attracted intensive academic and commercial attention due to its extremely high theoretical capacity. However, it is still far away from practical application because of its fast capacity fading, which is caused by the huge volume change. Here, a novel network polymer binder is synthesized through in situ thermal crosslinking of water‐soluble carboxymethyl cellulose (CMC) and maleic anhydride (MAH). The as‐obtained polymer binder network can effectively restrict the huge volume change of Si an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“… 138 The glycerol crosslinked PEDOT: PSS (GP) binder showed greatly enhanced peeling force and superior conductivity, leading to improved cycling and rate performances (1951.5 mA h g −1 after 200 cycles at 0.5 A g −1 and 804 mA h g −1 at a high current of 8.0 A g −1 ) of SiNP anodes containing no conductive additive. Maleic anhydride crosslinked corn starch 139 or CMC 140 binders have been demonstrated to be promising binders for the Si‐based anodes (Figure 12B). Besides, Song et al employed the inorganic sodium borate to crosslink CMC, making the obtained binder with strong ability to buffer the volume change of Si particles and maintain the integrity of overall electrode (Figure 12C).…”
Section: Designing Of Polymer Binders For Si‐based Anodesmentioning
confidence: 99%
See 1 more Smart Citation
“… 138 The glycerol crosslinked PEDOT: PSS (GP) binder showed greatly enhanced peeling force and superior conductivity, leading to improved cycling and rate performances (1951.5 mA h g −1 after 200 cycles at 0.5 A g −1 and 804 mA h g −1 at a high current of 8.0 A g −1 ) of SiNP anodes containing no conductive additive. Maleic anhydride crosslinked corn starch 139 or CMC 140 binders have been demonstrated to be promising binders for the Si‐based anodes (Figure 12B). Besides, Song et al employed the inorganic sodium borate to crosslink CMC, making the obtained binder with strong ability to buffer the volume change of Si particles and maintain the integrity of overall electrode (Figure 12C).…”
Section: Designing Of Polymer Binders For Si‐based Anodesmentioning
confidence: 99%
“…Other esterification reaction between -OH and sulfonic acid, 138 anhydride, 139,140 or boronic acid 141,142 groups can also be employed to fabricate the covalently crosslinked polymer binders for Si-based anodes. Qian et al reported an crosslinked conductive binder for SiNP anodes by thermally crosslinking PEDOT: PSS and glycerol at 180 C (Figure 12A).…”
Section: Covalently Crosslinked Polymer Bindersmentioning
confidence: 99%
“…Besides, the binder plays a crucial role in high‐capacity alloy‐typed anodes. [ 20‐23 ] And there have been excellent cases through optimizing the binders in achieving high electrochemical performance Si anodes, [ 24 ] such as cross‐linking network polymer, [ 25‐27 ] self‐healing binders, [ 28‐30 ] and conductive binders. [ 31,32 ] Moreover, it is accepted that the SEI layer is formed on the surface of anode electrode under low potential due to electrolyte decomposition during the initial cycles.…”
Section: Introductionmentioning
confidence: 99%
“…The Fourier‐transform infrared (FTIR) spectra of all the MP−Si@C composites in the 400–4000 cm −1 wavenumber range are presented in Figure 1(d). Moreover, the characteristic absorption peaks for the vibration of the Si−Si and Si−O−Si bonds at 451 and at 1053 cm −1 , respectively, and the absorption bands corresponding to the vibration of the C−H, C=C, and C−C bonds were observed in the FTIR spectra of the MP−Si@C composites in the wavenumber range of 1100–2200 cm −1 [33,34] …”
Section: Resultsmentioning
confidence: 94%